Understanding geometric algebra : Hamilton, Grassmann, and Clifford for computer vision and graphics - Kanatani, Kenʼichi, 1947- (Online access with DDA: Askews (Maths), 2015)
Introduction. 3-D Euclidean Geometry. Oblique Coordinates Systems. Hamilton's Quaternion Algebra. Grassmann's Outer Product Algebra. Geometric Product and Clifford Algebra. Homogeneous Space and Grassmann-Cayley Algebra. Conformal Space and Conformal Geometry. Geometry of Camera Imaging. Bibliography. Answers of Exercises.